2021
DOI: 10.1177/00938548211010316
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Brain Injury in Community Corrections: Prevalence and Differences in Compliance and Long-Term Outcomes Among Men and Women on Probation

Abstract: There are 4.5 million adults in community corrections (e.g., probation and parole), nearly twice the number of people incarcerated in jails and prisons combined. Research suggests that more than half of men in jail have experienced at least one traumatic brain injury (TBI). Very little is known about TBI history in probation. This study reviewed TBI history, cognitive and psychosocial data, and judicial records. Results showed that 47% of persons on probation report TBI. People on probation with TBI also had c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…While there is no research that provides a causal link between TBI and criminal offending, studies have found TBI among justice-involved individuals to be as high as 10 times that in the general population. Research indicates that between 23-86% of individuals who are incarcerated have a history of TBI [1][2][3][4], significantly larger than estimates of TBI in the general population of 8.5% [5]. Like has been observed in adult populations, research has also found large proportions of youth in juvenile justice settings have a history of TBI [6,7].…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…While there is no research that provides a causal link between TBI and criminal offending, studies have found TBI among justice-involved individuals to be as high as 10 times that in the general population. Research indicates that between 23-86% of individuals who are incarcerated have a history of TBI [1][2][3][4], significantly larger than estimates of TBI in the general population of 8.5% [5]. Like has been observed in adult populations, research has also found large proportions of youth in juvenile justice settings have a history of TBI [6,7].…”
Section: Introductionmentioning
confidence: 94%
“…However, they did not find differences in rates of mental health or substance abuse between the groups. Gorgens et al found that women with TBI on probation have similar recidivism rates to men with TBI, though women without TBI had a lower risk of reoffending than men without TBI [1]. The authors also found that women with TBI were more likely than their male counterparts to have mental illness and substance use disorders [1].…”
Section: Sex Differences In Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Systematic reviews also reported prevalence rates of TBI of up to 100% across all ages ( 6 ), 72.1% among youths ( 7 ), and 85% among incarcerated adults ( 8 ). One study focusing on community corrections found a 47% prevalence rate of TBI among persons on probation ( 9 ). Studies that investigated sex-specific rates of TBI reported a 49% prevalence rate among female youths ( 10 ), 95% among female adult prisoners ( 10 ), and 63.7% among male adult prisoners ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…How individuals define and respond to supervision conditions is a "contextually contingent" [50] and "interactive" [51] process, "depending upon their previous experiences, background, social context, and expectations about the penalty" [50: p.382]. Differences in how conditions are set, monitored, and enforced can reinforce inequities-such as those tied to race [52], gender [53,54], and health [55]-which are further amplified by underfunding and increasing cuts to programming for mental health issues, substance use, and other transitionary planning [40].…”
Section: Introductionmentioning
confidence: 99%